2022
DOI: 10.1007/s15010-022-01886-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 condition is not only a question of persistent symptoms: structured screening including health-related quality of life reveals two separate clusters of post-COVID

Abstract: Purpose Some patients experience long-term sequelae after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, despite a present post-COVID condition, defined as “any symptom lasting longer than 12 weeks,” only a subset of patients search for medical help and therapy. Method We invited all adults with a positive real-time polymerase chain reaction (RT-PCR) for SARS-CoV-2 between March 2020 and September 2021 (n = 4091) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
0
13
0
4
Order By: Relevance
“…Thus, in a study by Giszas et al. ( 24 ), 70.7% of the participants reported persistent symptoms, while only one-third of those also reported that these symptoms significantly reduced their quality of life. Giszas et al.…”
Section: Long-covidmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, in a study by Giszas et al. ( 24 ), 70.7% of the participants reported persistent symptoms, while only one-third of those also reported that these symptoms significantly reduced their quality of life. Giszas et al.…”
Section: Long-covidmentioning
confidence: 94%
“…Giszas et al. ( 24 ) therefore proposed to distinguish between Long-COVID “disease”, in which quality of life is significantly diminished and Long-COVID “condition”, in which quality of life is near-normal. In summary, while not entirely conclusive, these rates indicate that a significant amount of individuals who have had COVID-19 may develop Long-COVID.…”
Section: Long-covidmentioning
confidence: 99%
“…The World Health Organization (WHO) defines these sequelae, by common usage now also referred to as “Long COVID”, as a post-COVID-19 condition that usually occurs three months after a confirmed or probable SARS-CoV-2 infection with a set of new-onset, persistent or fluctuating symptoms that last for at least two months ( 11 ). The most common symptoms in this context are fatigue, exercise intolerance, post-exertional malaise, difficulty breathing, headache, muscle pain, tachycardia, concentration deficits and diminished quality of life ( 12 15 ). In this context, it bears noting that the overall prevalence and types of symptoms can vary depending on the COVID-19 disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines these sequelae, by common usage now also referred to as "Long COVID", as a post-COVID-19 condition that usually occurs three months after a confirmed or probable SARS-CoV-2 infection with a set of new-onset, persistent or fluctuating symptoms that last for at least two months (11). The most common symptoms in this context are fatigue, exercise intolerance, post-exertional malaise, difficulty breathing, headache, muscle pain, tachycardia, concentration deficits and diminished quality of life (12)(13)(14)(15). The pathophysiological mechanisms involved in the devolvement of Long COVID remain to be elucidated, with a range of theories currently under discussion.…”
Section: Introductionmentioning
confidence: 99%